The Influence of Language Learning Anxiety on Speaking and Reading Performances in Foreign Language Context - Masrul; Erliana, Santi (STAIN Sultan Abdurrahman Kepulauan Riau, 2024)
Anxiety is a common feeling among language learners. This research investigated the impacts of language learning anxiety on English as Foreign Language (EFL) students' speaking and writing abilities. Data were collected from 102 EFL college students, to whom questionnaires were distributed to assess students' performance. Speaking and reading tests were also conducted, followed by semi-structured interviews to confirm the findings from the quantitative phase. The analysis of variance revealed significant results for speaking and reading anxiety which confirmed previous findings stating that high levels of anxiety negatively affected students’ speaking ability, while reading anxiety could facilitate language learning. In addition, social factors weaken students’ speaking performance, but the opportunity to use reading strategies could improve reading task performance. The implications of the research for speaking and reading anxiety were also discussed in this study.